Poverty, agricultural intensification, and the environment - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul (Pakistan Institute of Development Economics, 1994)
As the world's population increases by almost 100 million people each year during the next two to three decades-the largest annual population increase in history- agricultural intensification, i.e. production of more food on land already being cultivated, is a must. There is little scope for increasing cultivated land in Asia, North Africa, and Central America, while in Sub-Saharan Africa and South America, physical and technological constraints are likely to restrain large-scale conversion of potentially cultivable land [Dram and Hojjati (1994)]. Agricultural intensification is already the main source of increased food production. I Intensive use of chemical fertilizers, pesticides, and irrigation technology, in combination with higher-yielding crop varieties, has led to enough food being produced in the world such that if it were evenly distributed, no one would go hungry. Global food production per capita increased from about 260 kilograms (kgs) in 1950 to about 350 kgs in the early 1990s [FAD (1992)]. In developing countries the corresponding increase was from 170 kgs to 250 kgs.